2016
DOI: 10.1515/acph-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary in vitro evaluation of the anti-proliferative activity of guanylhydrazone derivatives

Abstract: Preliminary in vitro evaluation of the anti-proliferative activity of guanylhydrazone derivativesGuanylhydrazones have shown promising antitumor activity in preclinical tumor models in several studies.In this study, we aimed at evaluating the cytotoxic eff ect of a series of synthetic guanylhydrazones. Diff erent human tumor cell lines, by including HCT-8 (colon carcinoma), MDA-MB-435 (melanoma) and SF-295 (glioblastoma) were continuous exposed to guanylhydrazone derivatives for 72 hours and growth inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The analytical grade reagents were purchased from Sigma-Aldrich, Acros Chemical Co. or Merck. The substance LQM10 (2E)-2-(3,5-di-tert-butyl-4-hydroxybenzylidene)hydrazinecarboximidamide was synthesized using a previously described procedure [8].…”
Section: Materials and Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…The analytical grade reagents were purchased from Sigma-Aldrich, Acros Chemical Co. or Merck. The substance LQM10 (2E)-2-(3,5-di-tert-butyl-4-hydroxybenzylidene)hydrazinecarboximidamide was synthesized using a previously described procedure [8].…”
Section: Materials and Apparatusmentioning
confidence: 99%
“…Aminoguanidine hydrazine derivatives are bioactive compounds that have been intensively studied for their different (and interesting) biological activities, such as in the treatment of hypertension (Guanabenz) [1] [2] [3], or antiarrhythmic [4] [5]; nonpeptide NPFF1 Receptor Antagonists reverse opioid-induced hyperalgesia [6]; as modulators of norfloxacin resistance in S. aureus that overexpress the efflux pump of NorA [7]; and anticancer [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The title compounds were isolated after cooling to room temperature, being washed, or recrystallized using an appropriate solvent. Structural characterization of the products is described elsewhere [20,21]. LogP was calculated in the Hy-perChem™ software Release 8.0.8 Windows.…”
Section: Chemistrymentioning
confidence: 99%
“…They concluded that the 3-nitrophenyl and 4-nitrophenyl moieties are important pharmacophore groups which increase the affinity for specific tumor receptors [ 11 ]. Other research groups have synthesized new guanylhydrazones with anticancer activity in order to obtain new molecules for the treatment of this disease [ 12 ]. The guanylhydrazone derivatives 2-[(3,5-di- tert -butyl-4-hydroxyphenyl)methylene]hydrazinecarboximidamide (LQM10), 2-([1,10-biphenyl]4-ylmethylene)hydrazinecarboximidamide (LQM14) and 2-[(3,4-dichlorophenyl)-methylene]hydrazinecarboximidamide (LQM17) have shown pharmacological activity against some neoplastic cell lines, such as human colon (HCT-8), melanoma (MDA-MB435), glioblastoma (SF-295) and promyelocytic leukemia (HL-60) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%